Qualitative Study of Sukuk as an Alternative Sharia Financing and Its Impact on Economic Growth in Indonesia - Andi Sawe Ri Esso; Amiruddin K; Muhammad Amiruddin Abdullah (Journal of Economic Education and Entrepreneurship Studies, 2024)
This study aims to explore the role of sukuk as an alternative form of sharia financing in promoting economic growth in Indonesia. The study employs a qualitative approach, utilizing a literature review and relevant data from credible sources, such as the recapitulation of the sharia stock index presented by the Indonesia Stock Exchange. Findings indicate that the role of sharia bonds, specifically sukuk, has experienced substantial growth in Indonesia between 2000 and 2024. Sukuk plays a critical role in enhancing the national economy and improving public welfare. The market has demonstrated a high level of responsiveness to sukuk issuance, with almost all issued sukuk being fully absorbed, often with demand exceeding supply. To harness the potential of sukuk for broader economic benefits, it is crucial to undertake strategic steps, including public awareness campaigns to educate the wider community about the benefits and opportunities provided by sukuk as a sharia-compliant investment instrument. Increasing public understanding of sukuk will further support sustainable economic development and financial inclusion in Indonesia.